Device-measured sedentary behaviour and anxiety symptoms during adolescence: a 6-year prospective cohort study. Issue 14 (18th October 2022) - Kandola, A.; Lewis, G.; Osborn, D. P. J.; Stubbs, B.; Hayes, J. F.
Abstract: Background: Sedentary behaviour is potentially a modifiable risk factor for anxiety disorders, a major source of global disability that typically starts during adolescence. This is the first prospective study of associations between repeated, device-based measures of sedentary behaviour and anxiety symptoms in adolescents. Methods: A UK cohort with 4257 adolescents aged 12 at baseline (56% female). Main exposures were sedentary behaviour and physical activity measured using accelerometers for 7-days at ages 12, 14, and 16. Primary outcome was anxiety symptom scores at age 18 from a Clinical Interview Schedule-Revised. We used adjusted negative binomial regression and iso-temporal substitution methods to analyse the data. Results: We found a positive association between sedentary behaviour at ages 12, 14, and 16, with anxiety symptoms at age 18, independent of total physical activity volume. Theoretically replacing an hour of daily sedentary behaviour for light activity at ages 12, 14, and 16, was associated with lower anxiety symptoms by age 18 by 15.9% (95% CI 8.7–22.4), 12.1% (95% CI 3.4–20.1), and 14.7% (95% CI 4–24.2), respectively. Whereas, theoretically replacing an hour of sedentary behaviour with moderate-to-vigorous physical activity was not associated with differences in anxiety symptoms. These results were robust to a series of sensitivity analyses. Conclusion: Sedentary behaviour is a possible risk factor for increasing anxiety symptoms during adolescence, independent of total physical activity volume. Instead of focusing on moderate-to-vigorous activity, replacing daily sedentary behaviour with light activity during adolescence could be a more suitable method of reducing future anxiety symptoms.